Detailed electrical characterization of 200 mm CMOS compatible GaN/Si HEMTs down to deep cryogenic temperatures. (November 2022) - Kim, Donghyun; Theodorou, C.; Chanuel, A.; Gobil, Y.; Charles, M.; Morvan, E.; Woo Lee, Jae; Mouis, M.; Ghibaudo, G.
Highlights: Cryogenic electrical characterization of 200 mm CMOS compatible GaN/Si HEMTs. Transistor parameter extraction carried out down to very low temperature. Very good functionality of GaN/Si HEMTs demonstrated down to cryogenic temperatures. Improvement of mobility, subthreshold slope and saturation velocity at very low temperature. Source-drain series resistance more dominated by contact resistance than by 2DEG access region resistance at low temperature. Abstract: A detailed electrical characterization and transistor parameter extraction on 200 mm CMOS compatible GaN/Si HEMTs was performed down to deep cryogenic temperatures. The main transistor parameters (threshold voltage Vth, low-field mobility μ0, subthreshold swing SS, source-drain series resistance Rsd ) were extracted in linear region using the Y-function and the Lambert-W function methods for gate lengths down to 0.1 µm. The Y-function method was also employed in saturation region for the extraction of the saturation velocity. The results indicate that these GaN/Si HEMT devices demonstrate a very good functionality down to very low temperature with improvement of mobility and subthreshold slope. It was also shown by TLM analysis that the source-drain series resistance Rsd is more limited by the contact resistance than by the 2DEG access region resistance as temperature is lowered.